Environmental Approach Assisted by Realia Media in Science Learning in Elementary Schools - Kasimah; Oviana, Wati; Jannah, Misbahul (MANDAILING GLOBAL EDUKASIA, 2024)
Based on the results of observations and discussions with the class V teacher at sekolah dasar negeri Kajhu Aceh Besar, there were problems found in the science learning process, where students were less interested in the learning process provided by the teacher, such as a lack of student activity in searching for and finding new information to solve problems. Therefore, it is necessary to actively involve students in learning. This research aims to determine the application of the environmental approach assisted by realia media to improve student learning outcomes in class V science learning at the Kajhu State Elementary School, Aceh Besar. The method used in this research is Classroom Action Research. The data collection techniques used are observation and tests, the data analysis techniques used use the percentage formula. The results of the research showed that teacher activity in cycle I obtained a percentage of 77.88% in the good category, cycle II experienced an increase of 88.46% in the very good category. Student activities in cycle I obtained a percentage score of 80.76 in the good category, increasing in cycle II to 89.42% in the very good category. The increase in student learning outcomes in the first cycle was 52.63% in the poor category, and in the second cycle there was an increase of 90.47% in the very good category. So it can be concluded that the application of an environmental approach assisted by realia media can improve student learning outcomes at the Kajhu State Elementary School, Aceh Besar.